THE PEDAGOGICAL PRACTICE OF PHYSICAL EDUCATION TEACHERS IN THE EARLY YEARS OF ELEMENTARY SCHOO - Teixeira da Rocha , Ricardo; Olímpia Barbosa Silva , Vânia; Antônio de Araújo Leite Filho , Marcos (RENEF, 2022)
The pedagogical practice of Physical Education teachers has been the object of several academic researches in order to clarify its construction process, the concerns that guide its intention, as well as the challenges faced in the school reality. As a mandatory subject of basic education, Physical Education develops possibilities of movements, helps in the teaching and learning process of other subjects, promotes well-being actions, being an important axis of the school. Due to this relevance, the present research aims to investigate the pedagogical practice of Physical Education teachers in the early years of elementary school. For the feasibility of this study, a bibliographic review will be carried out together with a field research through the application of a questionnaire that will seek to identify how the pedagogical practice of Physical Education teachers in the early years of elementary school happens; how the teaching strategies of the research subjects are planned; and to know the reality of the daily life of Physical Education teachers in public schools.